2020
DOI: 10.3390/insects11010044
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of d-Limonene and β-Ocimene as Attractants of Aphytis melinus (Hymenoptera: Aphelinidae), a Parasitoid of Aonidiella aurantii (Hemiptera: Diaspididae) on Citrus spp.

Abstract: The volatile organic compounds (VOCs) released from herbivore-infested plants can be used as chemical signals by parasitoids during host location. In this research, we investigated the VOC chemical signals for the parasitoid Aphytis melinus to discriminate between Aonidiella aurantii (California red scale)-infested fruit and non-infested fruit on three different citrus species. First, we identified the chemical stimuli emanating from non-infested and A. aurantii-infested citrus fruits via solid phase microextr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
35
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(39 citation statements)
references
References 29 publications
3
35
1
Order By: Relevance
“…Although D-limonene was the dominant compound detected in citrus plants, there were no variations in the amounts released after herbivore damage. Contrary to this result, Mohammed et al (2020) found that D-limonene levels sharply increased in several Citrus species after infestation with the pest Aonidiella aurantii (Maskell) (Hemiptera: Diaspididae), and that its parasitoid, Aphytis melinus DeBach (Hymenoptera: Aphelinidae), was attracted to this volatile combined with β-Ocimene. This last compound is released by grapevines plants after feeding and oviposition of the proconiini sharpshooter Homalodisca vitripennis (Germar) and it affects the foraging behavior of the egg parasitoid Cosmocomoidea ashmeadi Girault (formerly Gonatocerus), which positively responded to this volatile when it was combined with α-farnesene (Krugner et al 2014).…”
Section: Discussioncontrasting
confidence: 69%
“…Although D-limonene was the dominant compound detected in citrus plants, there were no variations in the amounts released after herbivore damage. Contrary to this result, Mohammed et al (2020) found that D-limonene levels sharply increased in several Citrus species after infestation with the pest Aonidiella aurantii (Maskell) (Hemiptera: Diaspididae), and that its parasitoid, Aphytis melinus DeBach (Hymenoptera: Aphelinidae), was attracted to this volatile combined with β-Ocimene. This last compound is released by grapevines plants after feeding and oviposition of the proconiini sharpshooter Homalodisca vitripennis (Germar) and it affects the foraging behavior of the egg parasitoid Cosmocomoidea ashmeadi Girault (formerly Gonatocerus), which positively responded to this volatile when it was combined with α-farnesene (Krugner et al 2014).…”
Section: Discussioncontrasting
confidence: 69%
“…More mealybugs were parasitized on cyclolavandulyl butyrate‐treated trees 58 . d ‐Limonene and β‐ocimene were significantly increased in fruit infested with Aonidiella aurantii and elicited a strong attraction for Aphytis melinus parasitoids 59 . Applications of these semiochemicals in the field may greatly enhance the efficiency of biological control of A. aurantia 60 .…”
Section: Discussionmentioning
confidence: 99%
“…58 D-Limonene and ⊎-ocimene were significantly increased in fruit infested with Aonidiella aurantii and elicited a strong attraction for Aphytis melinus parasitoids. 59 Applications of these semiochemicals in the field may greatly enhance the efficiency of biological control of A. aurantia. 60 We also discovered that volatiles from honeydew produced by P. solenopsis were attractive to A. bambawalei, therefore treatments with more honeydew on www.soci.org C Xu et al…”
Section: Discussionmentioning
confidence: 99%
“…The aphid solitary endoparasitoid Aphelinus varipes Foerster (Hymenoptera: Aphelinidae) is being used as a control measure against the Russian wheat aphid Diuraphis noxia (Mordwilko) in Australia [ 23 ] and the USA [ 24 ]; M. persicae in Canada [ 25 ] and China [ 26 ]; and Rhopalosiphum padi , R. maidis and Macrosiphum euphorbiae in other regions [ 27 , 28 ]. Parasitoids use HIPVs to locate their prey [ 29 , 30 ]; as indicated by Mohammed et al (2020) [ 31 ], Aphytis melinus (DeBach; Hymenoptera: Aphelinidae) is significantly attracted towards HIPVs emitted by Aonidiella aurantii -fed citrus plants. The aim of the present study was thus to assess whether HIPVs can mediate the parasitoid behavior in the tritrophic interactions among A. varipes , M. persicae and host plants.…”
Section: Introductionmentioning
confidence: 99%